Förster resonance energy transfer mediated enhancement of the fluorescence lifetime of organic fluorophores to the millisecond range by coupling to Mn-doped CdS/ZnS quantum dots. (16th December 2015) - Kaiser, Uwe; Sabir, Nadeem; Carrillo-Carrion, Carolina; del Pino, Pablo; Bossi, Mariano; Heimbrodt, Wolfram; Parak, Wolfgang J
Abstract: Manganese-doped CdS/ZnS quantum dots have been used as energy donors in a Förster-like resonance energy transfer (FRET) process to enhance the effective lifetime of organic fluorophores. It was possible to tune the effective lifetime of the fluorophores by about six orders of magnitude from the nanosecond (ns) up to the millisecond (ms) region. Undoped and Mn-doped CdS/ZnS quantum dots functionalized with different dye molecules were selected as a model system for investigating the multiple energy transfer process and the specific interaction between Mn ions and the attached dye molecules. While the lifetime of the free dye molecules was about 5 ns, their linking to undoped CdS/ZnS quantum dots led to a long effective lifetime of about 150 ns, following a non-exponential transient. Manganese-doped core–shell quantum dots further enhanced the long-lasting decay time of the dye to several ms. This opens up a pathway to analyse different fluorophores in the time domain with equal spectral emissions. Such lifetime multiplexing would be an interesting alternative to the commonly used spectral multiplexing in fluorescence detection schemes.